High minority power facilitates democratization across ethnic fault lines - Luke Glowacki; Florian Morath; Hannes Rusch (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
The historical record knows only few instances of democracies waging war against each other. Therefore, democratization is considered key in achieving global peace. However, efforts to achieve sustained democratic governance often fail-Afghanistan being a recent example. Democratization appears particularly challenging where grievances between ethnic groups can spill over into democratic institutions and obstruct the negotiation of mutually beneficial compromises. So far, research on democratization vis-à-vis preexisting ethnic conflict has relied on correlational evidence and historical case studies, making it hard to establish causality. Here, we complement previous work with an economic lab-in-the-field experiment modeling a situation in which unequal groups with ongoing ethnic tensions can solve a joint allocation problem either democratically or aggressively. We find that, as theoretically predicted, minority groups are much more likely to opt for inefficient aggression, but also that equipping minorities with high power under the democratic allocation procedure substantially reduces this problem. Removing ethnic hostility subtly shifts participants' beliefs but does not reduce aggressive behavior. Thus, our results demonstrate that well-designed democratic institutions can achieve efficient, peaceful outcomes even when intergroup hostility is prevalent. However, we also see that their success vitally depends on their inclusivity towards the interests of minority groups.
Keywords: 330; democratization; ethnicity; intergroup conflict; warfare; peace-making; minority power